Rôle de l’herbier Ruppia Sp. Dans la distribution de la malacofaune de la lagune Mellah - TALEB Sabri (My University, 2019)
Mellah Lagoon is an integral part of El- Kala National Park and is traditionally farmed. The economic need and the ecological context of the lagoon have enhanced this limited extent. The objectives of the present study is the description of the benthic malacofauna of the Mellah lagoon and its interaction with the substrate, mainly the Ruppia sp herbarium, to also know the importance of the marine current that enters the lagoon by the phenomenon swamps on the abundance and species richness of molluscs. During the study period (March 2019), the inventory of the malacological fauna of the Mellah lagoon allowed the identification of 7 species (4 bivalves and 3 gastropods). The highest specific wealth was recorded north- west of the lagoon in the herb-covered part Ruppia sp with 7 species. The maximum density recorded in the Ruppia sp section was 6240ind / m² at sector 2 level. On the other hand, and exceptionally, the zone with no herbarium shows a maximum density of 13856ind / m² (station 29). In addition, the clogging condition of the channel of communication with the sea plays a decisive role in the distribution of benthic macrofauna in general and that of malacofauna in particular. The lagoon is dominated by the mollusc Brachidontes marioni(Locard, 1889), arriving at times with a dominance of about 90% at sector 3 (part without herbarium). -------------------------------------------------------------------------------- بحيرة الملاح هي جزء لا يتجزأ من القالة الوطنية بارك ويتم زراعته بشكل تقليدي. وقد عززت الحاجة الاقتصادية والسياق البيئي للبحيرة هذا النطاق المحدود. أهداف الدراسة الحالية هي وصف الكائنات الحيوانية القاعية في بحيرة الملاح وتفاعلها مع الركيزة، وخاصة معشبة روبيا sp، لنعرف أيضًا أهمية التيار البحري الذي يدخل البحيرة عن طريق المستنقعات الظاهرة على وفرة وثراء أنواع الرخويات. تم خلال فترة الدراسة (مارس 2019) حصر الحيوانات الملاحية سمحت البحيرة بتحديد 7 أنواع (4 ذوات الصدفتين و3 بطنيات الأقدام). الاعلى تم تسجيل ثروة محددة شمال غرب البحيرة في الجزء المغطى بالأعشاب Ruppia sp مع 7 أنواع. بلغت الكثافة القصوى المسجلة في قسم Ruppia sp 6240 هند / م 2 عند مستوى القطاع 2. من ناحية أخرى، وبشكل استثنائي، فإن المنطقة التي لا تحتوي على معشبة تظهر كثافة قصوى تبلغ 13856 هند/م2 (المحطة 29). بالإضافة إلى حالة انسداد القناة يلعب التواصل مع البحر دورًا حاسمًا في توزيع الحيوانات الكبيرة القاعية بشكل عام والحيوانات الصغيرة بشكل خاص. تهيمن الرخويات Brachidontes marioni (لوكارد، 1889) على البحيرة، حيث تصل في بعض الأحيان بهيمنة حوالي 90% في القطاع 3 (جزء بدون المعشبة). ------------------------------------------------------------------------------------- La lagune de Mellah fait partie intégrante du parc national d'El-Kala. Parc et est cultivé de manière traditionnelle. La nécessité économique et le contexte écologique de la lagune ont renforcé cette étendue limitée. Les objectifs de la présente étude sont la description de la malacofaune benthique de la lagune du Mellah et son interaction avec le substrat, principalement l'herbier Ruppia sp, connaître également l'importance du courant marin qui entre dans la lagune par le phénomène des marécages sur le abondance et richesse spécifique des mollusques. Durant la période d'étude (mars 2019), l'inventaire de la faune malacologique du Mellah la lagune a permis l'identification de 7 espèces (4 bivalves et 3 gastéropodes). Le plus haut Une richesse spécifique a été enregistrée au nord-ouest de la lagune dans la partie herbacée Ruppia sp avec 7 espèces. La densité maximale enregistrée dans la section Ruppia sp était de 6240ind/m² au niveau du secteur 2. En revanche et exceptionnellement, la zone sans herbier présente une densité maximale de 13856ind/m² (station 29). De plus, l'état de colmatage du canal de la communication avec la mer joue un rôle déterminant dans la répartition de la macrofaune benthique en général et celle de la malacofaune en particulier. Le lagon est dominé par le mollusque Brachidontes marioni(Locard, 1889), arrivant parfois avec une dominance d'environ 90% au secteur 3 (partie sans herbier).